Sh*t my dad says - Halpern, Justin, 1980- (!t Books/HarperColllins, 2010)
A hilarious coming-of-age book about a son's relationship with his foul-mouthed father, written by a 29-year-old comedy writer who created the massively popular Twitter feed of the same name.